Predictive factors for clinical cure in the treatment of HBeAg(−) chronic hepatitis B or compensated cirrhosis: a prospective observational study - Lv, Yan-Qing; Guo, Ru-Hua; Liu, Kun-Yu; Li, Jia-Jie; Ji, Hui-Fan (Frontiers in Medicine, 2025)
BackgroundSequential or combined treatment with nucleos(t)ide analogs (NAs) and pegylated interferon alpha-2b (Peg-IFN-α-2b) can improve the clinical cure rate. However, its clinical application is limited due to the adverse reactions associated with IFN.MethodsA multi-center prospective observational study was conducted involving 59 NAs-treated chronic hepatitis B (CHB) patients who were treated with a combination therapy of NAs and Peg-IFN-α-2b for 48 weeks. Another 327 NAs-treated patients received NAs monotherapy for 48 weeks. At the end of the treatment, patients were classified into either the clinically cured group or the non-clinically cured group based on clinical efficacy. The study aimed to analyze the clinical cure rate and the predictive factors.ResultsAfter propensity score matching (PSM), a total of 104 patients were included in the exposure and the control groups. After 48 weeks of treatment, 13 patients in the exposed group achieved clinical cure, with a cure rate of 25%. In contrast, in the control group was 1.92%. The clinical cure rate was greater in the population with CHB or compensated cirrhosis treated with sequential or combined Peg-IFN-α-2b and NAs than in the control group (p < 0.001). Patients treated with Peg-IFN-α-2b were divided into a clinical cure group and a non-clinical cure group for single-factor regression and multi-factor binary logistic regression. The results showed that baseline qHBsAg [relative ratio (RR) = 0.997, 95%CI: [0.995, 0.999], p = 0.031] and △TBiL (RR = 0.698, 95%CI: [0.555, 0.879], p = 0.002) were independent influencing factors for achieving clinical cure in patients with CHB or compensated cirrhosis.ConclusionA lower baseline qHBsAg and decrease in TBiL at 24 weeks of treatment are independent influencing factors for achieving clinical cure. The lower the baseline qHBsAg and the higher the △TBiL levels after 24 weeks of treatment, the higher the probability of patients achieving clinical cure.